2012
DOI: 10.1007/s10792-012-9647-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute stroke after intravitreal bevacizumab to treat choroidal neovascularization due to angioid streaks in pseudoxanthoma elasticum

Abstract: To report the occurrence of acute stroke after intravitreal bevacizumab administration to treat choroidal neovascularization due to angioid streaks in a patient affected by pseudoxanthoma elasticum. A 54-year-old man with pseudoxanthoma elasticum had vision loss because of choroidal neovascularization due to angioid streaks. He underwent two intravitreal bevacizumab injections. Three days after the second procedure the patient was afflicted by acute stroke. Intravitreal injection of bevacizumab to treat choroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Several studies have shown that anti-VEGF injections can be used safely to treat patients. 2–4,6 However, Besozzi et al 7 discussed a patient who had an acute stroke after receiving a bevacizumab injection and raised concern over using bevacizumab off-label to treat patients with CNV secondary to PXE. This is due to the fact that PXE seems to be associated with increased risk of developing a stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that anti-VEGF injections can be used safely to treat patients. 2–4,6 However, Besozzi et al 7 discussed a patient who had an acute stroke after receiving a bevacizumab injection and raised concern over using bevacizumab off-label to treat patients with CNV secondary to PXE. This is due to the fact that PXE seems to be associated with increased risk of developing a stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Besozzi et al . [ 24 ] have reported acute stoke within 3 days of injection in a patient with PXE and no other systemic illness. Although one patient in our cohort developed two thromboembolic events, it is difficult to establish a causal relationship with IVB as he had other risk factors such as systemic hypertension and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear correlation between cerebral infarction and bevacizumab although the conclusion is based on individual cases. [ 7 ] However, the large-sample-based data analyses by Campbell et al . [ 8 9 ] indicated that the incidence of ischemic stroke was not significantly different between the bevacizumab treating group and control group.…”
Section: Discussionmentioning
confidence: 99%